Comparing the criminal careers of organized crime offenders in Italy and the Netherlands - Calderoni, Francesco (European journal of criminology, 2024)
The concept of organized crime has dynamically evolved, with researchers contending that it is a social construct or an umbrella concept encompassing different empirical manifestations. Scholars have often suggested classifying organized crime groups into those involved in ?racketeering? or ?governing? and those engaged in ?transit crime? or ?trading.? However, these propositions were never assessed at the level of individual criminal careers. We address two primary objectives: first, we test differences in the criminal careers of organized crime offenders between organized crime contexts that are historically different?comparing Italy, which is primarily known for racketeering organized crime, to the Netherlands, which is characterized more by transit crime. Second, we explore differences between criminal careers of organized crime offenders born in different decades; doing so allows us to measure differences in offending patterns in shifting organized crime contexts due to broader social changes while considering more country-specific changes in law enforcement and organized crime policies. The study relies on the criminal careers of 4480 organized crime offenders in Italy (n?=?3360) and the Netherlands (n?=?1120). We analyze the distributions of criminal career parameters, crime categories, age-crime curves, and offending trajectories. Offenders in Italy exhibit higher offending, earlier violence, earlier onset, and decline; offenders in the Netherlands display later onset, slower decline, and a greater involvement in drug and property offenses. Also, both samples show generalist offending patterns, long-lasting careers, and involvement in organized crime in adulthood. We also find substantial variation across decades of birth, with younger offenders in both countries reporting higher frequencies. We attribute this to the interplay of increased offending among younger individuals, the implicit selection bias in the sampling, and greater law enforcement pressure due to stricter anti-organized crime policies since the 1980s and 1990s.